Preparation method of transparent high-temperature-resistant PVC (polyvinyl chloride) crystal plate
By blending modified POE resin with PVC and using homemade heat-resistant crosslinking agent, a dense network structure is formed, which solves the problem of easy degradation of PVC crystal panels at high temperatures, and achieves both high temperature resistance and transparency.
Patent Information
- Application Number
- CN202411651618.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-11-19
AI Technical Summary
Existing PVC crystal panels are prone to degradation at high temperatures, resulting in poor high temperature resistance, affecting service life and aesthetics.
Modified POE resin is used to blend it with PVC, and add homemade heat-resistant crosslinking agent, and use materials such as N-phenylmaleimide crosslinking agent and terminal hydroxyl polydimethylsiloxane to form a dense network structure to Improve heat resistance while maintaining transparency.
It significantly improves the high temperature resistance and transparency of PVC crystal panels, extends the service life, and avoids poor weather resistance caused by ordinary modified copolymers.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic processing, in particular to a method for preparing a transparent high-temperature resistant PVC crystal plate. Background Art
[0002] Now, a new type of material, soft glass, is replacing glass and becoming people's new favorite. At work, it is widely used in electronics, chemistry, pharmaceuticals, food factories, clothing factories, work platforms, machine surfaces, various office desks, etc. In family life, it is widely used on the surface of glass materials, which can not only reflect the true color of glass and fashion, but also prevent the surface of glass furniture from being scratched. Crystal board is actually a PVC transparent soft board, a high-quality plastic composite material with a smooth, bright and transparent surface, no cracks, no bubbles, and uniform color.
[0003] Polyvinyl chloride resin has been widely used as a general-purpose resin. When used alone, its optical properties are good, but its mechanical and physical properties are not very good, especially in terms of high temperature strength. In order to improve its high temperature resistance, it is necessary to add various modifiers to modify the material. The substituted chlorine groups contained in the PVC molecular structure easily lead to the dehydrochlorination reaction of the PVC resin, thereby causing the degradation reaction of PVC. PVC is extremely unstable to heat, and the increase in temperature will greatly promote the dehydrochlorination reaction of PVC, thereby causing harm to the human body using the crystal plate, and will also reduce the aesthetics of the crystal plate, resulting in the disadvantage of a short service life. How to improve the high temperature resistance of the PVC crystal plate while ensuring its transparency is the focus of the present invention. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a transparent high-temperature resistant PVC crystal plate to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a transparent high temperature resistant PVC crystal plate, comprising the following preparation steps: (1) A three-necked flask is continuously filled with inert gas. After the air is expelled, 60 parts of deionized water, 0.16-0.18 parts of emulsifier, and 0.1 parts of potassium persulfate are added, and the mixture is heated and stirred at a speed of 60 rpm and a heating rate of 10°C / min. When the temperature reaches 70°C, a mixed solution of 0.3-0.5 parts of allyl methacrylate and 16-19 parts of 2-phenyl-1,3-butadiene is added dropwise. After the addition is completed, stirring is continued for 1 hour at a stirring rate of 150-250 rpm. A mixed solution of 3-5 parts of N-phenylmaleimide, 0.1 parts of potassium persulfate, and 3-4 parts of deionized water is added dropwise. After the addition is completed, stirring is continued for 1 hour at a stirring rate of 150-250 rpm to obtain an elastomer latex. (2) A three-necked flask is continuously filled with inert gas, and 17-19 parts of elastomer latex, 50 parts of deionized water, and 0.1 parts of potassium persulfate are added, and heated to 70°C with stirring at a speed of 60 rpm and a heating rate of 10°C / min; then 3.5-4 parts of glycidyl methacrylate are added dropwise for 30 minutes; after reacting for 1 hour, 3-4 parts of styrene are added dropwise for 30 minutes and maintained for 1 hour; after salting out and condensing with aluminum chloride solution, the filtrate is filtered and centrifuged for dehydration, washed with deionized water 3 times, and dried at 50°C for 5-8 hours to obtain a powdered polymer heat-resistant crosslinking agent; (3) Octamethyltetrasiloxane, hydroxy silicone oil and catalyst are mixed in a weight ratio of 100:0.1-0.2:0.3-0.5, added to a three-necked flask, evacuated to 0.01MPa at 60°C, then introduced nitrogen, heated to 80-100°C, reacted for 1-3h; heated to 100-120°C, continued to react for 1-3h; then heated to above 160-180°C and evacuated for 0.5-1.5h to obtain terminal hydroxyl polydimethylsiloxane; weigh 2-3 parts of maleic anhydride and 0.2-4 parts of terminal hydroxyl polydimethylsiloxane, add to a beaker Pour 20 parts of acetone into the mixture to dissolve it, and stir at 120rpm until it is completely dissolved; then pour the dissolved mixed solution into a high-speed mixer containing POE and stir for 5 minutes at a stirring speed of 400rpm; finally, inject the mixed material into a twin-screw extruder, wherein the extruder barrel head temperature is 170-190℃, the main engine speed is 300r / min, the feed speed is 10r / min, and the vacuum degree of the vacuum section is 0.05-0.09MPa; the twin-screw extruder is extruded into filaments, then cooled with deionized water, and finally dried at room temperature for 24h to obtain the modified POE resin; (4) 100 parts of PVC resin, 2-3 parts of stabilizer, 8-18 parts of modified POE resin, 50-55 parts of trioctyl trimellitate, and 0.5-0.8 parts of heat-resistant crosslinking agent are accurately weighed according to the formula, put into a high-speed mixer and mix at a speed of 1250-1450 rpm. When the temperature rises to 95-105°C, discharge the material into a low-speed mixer at a speed of 70-100 rpm and cool to 25-35°C before discharging; then add the material to a double-roll open mill and mix to produce a sheet. The roll temperature of the double-roll open mill is 110-120°C; finally, the sheet is pressed in a molding machine at 160-180°C for 8-10 minutes and then cooled to obtain a transparent high-temperature resistant PVC crystal plate.
[0006] Furthermore, the emulsifier in step (1) is an anionic emulsifier OT.
[0007] Furthermore, the dropping time in step (1) is 1 hour.
[0008] Furthermore, the inert gas in steps (1) and (2) is nitrogen.
[0009] Furthermore, in step (2), the centrifugal speed is 12000-20000 rpm, and the time is 20 min.
[0010] Furthermore, the catalyst in step (3) is tetramethylammonium hydroxide siliconate.
[0011] Furthermore, in step (3), the weight ratio of POE to the mixed solution is 100:0.5-1.5.
[0012] Furthermore, in step (3), the temperature of the high-speed stirrer during stirring is 200-300°C.
[0013] Furthermore, in step (4), the stabilizer is liquid barium zinc.
[0014] Furthermore, the mixing time in step (4) is 300-500s.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention blends modified POE resin with PVC and adds a self-made heat-resistant cross-linking agent to achieve high temperature resistance and high transparency.
[0016] First, during the emulsion polymerization of acrylic acid ester and 2-phenyl-1,3-butadiene monomer, an N-phenylmaleimide crosslinking agent is added to ensure the optical properties of the crystal plate and improve its high temperature resistance. The crosslinking agent has a five-membered cyclic monomer with a 1,2-disubstituted vinyl structure. When embedded in the polymer chain, it can increase the block's internal rotation resistance, thereby improving the polymer's heat resistance. In this process, a styrene-acrylic binary copolymer is prepared by a soap-free emulsion polymerization method. Due to the block crosslinking characteristics, the common modified copolymer with an added elastomer component has a large number of unsaturated carbon-carbon double bonds in the molecular chain, which leads to poor weather resistance and easy aging of the crystal plate during long-term use, thereby reducing its high temperature resistance. After obtaining the acrylic elastomer colloid, methacrylic acid glycidyl is grafted with styrene in steps to form a polymer. The copolymer is added to the PVC resin as a heat-resistant crosslinking agent to improve its high temperature resistance. During the polymerization of ethylene, methacrylic acid glycidyl causes the epoxy group to be located on the side chain to form an O-type polymer, which effectively ensures the light transmittance of the resin. Secondly, octamethyltetrasiloxane is subjected to ring-opening polymerization in an alkaline environment to obtain terminal hydroxyl polydimethylsiloxane, and then the terminal hydroxyl polydimethylsiloxane is grafted and modified with a POE resin matrix through maleic anhydride, and the heat resistance of the modified melt-granulated POE resin is optimized, and then blended with PVC resin, and the soft chain curling structure of octene and the crystallized ethylene chain are used as physical cross-linking points. After the two modified resins are blended, a dense network structure can be formed to achieve a very excellent heat-resistant effect; in addition, the strictly selected POE resin and the addition of various modifiers in the present invention also ensure the transparency of the prepared crystal plate, and the high temperature resistance is improved without affecting its transmittance. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of a transparent high temperature resistant PVC crystal plate prepared in the following examples are as follows: Transparency: The samples of the embodiment and the comparative example were made into crystal plates with a thickness of 1 cm, and the light transmittance test was conducted according to the standard GB / T2410-2008.
[0019] High temperature resistance: The samples of the embodiments and comparative examples were made into crystal plates with a thickness of 1 cm and tested according to the Congo red method described in GB / T 2917.1-2002 at a test temperature of 180°C.
[0020] Example 1; (1) A three-necked flask was continuously filled with nitrogen. After the air was expelled, 60 parts of deionized water, 0.16 parts of anionic emulsifier OT, and 0.1 parts of potassium persulfate were added, and the mixture was heated and stirred at a stirring speed of 60 rpm and a heating rate of 10°C / min; when the temperature was raised to 70°C, 0.3 parts of a mixed solution of allyl methacrylate and 16 parts of 2-phenyl-1,3-butadiene were added dropwise for 1 hour. After the addition was completed, the mixture was stirred for 1 hour at a stirring rate of 150 rpm; a mixed solution of 3 parts of N-phenylmaleimide, 0.1 parts of potassium persulfate, and 3 parts of deionized water was added dropwise for 1 hour. After the addition was completed, the mixture was stirred for 1 hour to obtain an elastomer latex at a stirring rate of 150 rpm; (2) A three-necked flask is continuously filled with nitrogen, and 17 parts of elastomer latex, 50 parts of deionized water, and 0.1 parts of potassium persulfate are added. The mixture is heated and stirred to 70°C at a stirring speed of 60 rpm and a heating rate of 10°C / min. Then, 3.5 parts of glycidyl methacrylate are added dropwise for 30 minutes. After the reaction lasts for 1 hour, 3 parts of styrene are added dropwise for 30 minutes and maintained for 1 hour. After salting out and condensing with aluminum chloride solution, the filtrate is filtered and centrifuged at a speed of 12,000 rpm for 20 minutes. The filtrate is washed with deionized water three times and dried at 50°C for 5 hours to obtain a powdered polymer heat-resistant crosslinking agent. (3) Octamethyltetrasiloxane, hydroxy silicone oil and catalyst tetramethylammonium hydroxide silicon alkoxide were mixed in a weight ratio of 100:0.1:0.3, added to a three-necked flask, evacuated to 0.01 MPa at 60°C, and then nitrogen was introduced. The temperature was raised to 80°C and reacted for 1 hour; the temperature was raised to 100°C and the reaction was continued for 1 hour; the temperature was raised to above 160°C and evacuated for 0.5 hour to obtain terminal hydroxyl polydimethylsiloxane; 2 parts of maleic anhydride and 0.2 parts of terminal hydroxyl polydimethylsiloxane were weighed and added to a beaker, 20 parts of acetone were poured in to dissolve it, and the mixture was stirred at 120 rpm. Stir until completely dissolved; then pour the dissolved mixed solution into a high-speed mixer containing POE and stir for 5 minutes, the temperature is 200℃, the stirring speed is 400rpm, and the weight ratio of POE to the mixed solution is 100:0.5; finally, inject the mixed material into a twin-screw extruder, wherein the extruder barrel head temperature is 170℃, the main engine speed is 300r / min, the feed speed is 10r / min, and the vacuum degree of the vacuum section is 0.05MPa; the twin-screw extruder is extruded into filaments, then cooled with deionized water, and finally dried at room temperature for 24h to obtain the modified POE resin; (4) 100 parts of PVC resin, 2 parts of stabilizer liquid barium zinc, 8 parts of modified POE resin, 50 parts of trioctyl trimellitate, and 0.5 parts of heat-resistant crosslinking agent are accurately weighed according to the formula, put into a high-speed mixer and mix at a speed of 1250 rpm. When the temperature rises to 95°C, discharge the material into a low-speed mixer at a speed of 70 rpm and cool to 25°C before discharging; then add the material to a double-roll open mill and mix to form a sheet for 300 seconds at a roll temperature of 110°C; finally, the sheet is pressed in a molding machine at 160°C for 8 minutes and then cooled to obtain a transparent high-temperature resistant PVC crystal plate.
[0021] Example 2; (1) A three-necked flask was continuously filled with nitrogen. After the air was expelled, 60 parts of deionized water, 0.17 parts of anionic emulsifier OT, and 0.1 parts of potassium persulfate were added, and the mixture was heated and stirred at a stirring speed of 60 rpm and a heating rate of 10°C / min; when the temperature was raised to 70°C, 0.4 parts of a mixed solution of allyl methacrylate and 17.5 parts of 2-phenyl-1,3-butadiene were added dropwise for 1 hour. After the addition was completed, stirring was continued for 1 hour at a stirring rate of 200 rpm; a mixed solution of 4 parts of N-phenylmaleimide, 0.1 parts of potassium persulfate, and 3.5 parts of deionized water was added dropwise for 1 hour. After the addition was completed, stirring was continued for 1 hour to obtain an elastomer latex at a stirring rate of 200 rpm; (2) A three-necked flask is continuously filled with nitrogen, and 18 parts of elastomer latex, 50 parts of deionized water, and 0.1 parts of potassium persulfate are added. The mixture is heated and stirred to 70°C at a stirring speed of 60 rpm and a heating rate of 10°C / min. Then, 3.75 parts of glycidyl methacrylate are added dropwise for 30 minutes. After the reaction lasts for 1 hour, 3.5 parts of styrene are added dropwise for 30 minutes and maintained for 1 hour. After salting out and condensing with aluminum chloride solution, the filtrate is filtered and centrifuged for dehydration at a centrifugal speed of 16,000 rpm for 20 minutes. The filtrate is washed with deionized water three times and dried at 50°C for 6.5 hours to obtain a powdered polymer heat-resistant crosslinking agent. (3) Octamethyltetrasiloxane, hydroxy silicone oil and catalyst tetramethylammonium hydroxide siliconate were mixed in a weight ratio of 100:0.15:0.4, added to a three-necked flask, evacuated to 0.01 MPa at 60°C, and then nitrogen was introduced. The temperature was raised to 90°C and reacted for 1.5 hours; the temperature was raised to 110°C and the reaction was continued for 1.5 hours; the temperature was raised to above 170°C and evacuated for 1 hour to obtain terminal hydroxyl polydimethylsiloxane; 2.5 parts of maleic anhydride and 2.1 parts of terminal hydroxyl polydimethylsiloxane were weighed and added to a beaker, and 20 parts of acetone were poured in to dissolve them. The mixture was heated for 120 hours. pm speed until completely dissolved; then pour the dissolved mixed solution into a high-speed mixer containing POE and stir for 5 minutes, the temperature is 250℃, the stirring speed is 400rpm, and the weight ratio of POE to the mixed solution is 100:1; finally, inject the mixed material into a twin-screw extruder, wherein the extruder barrel head temperature is 180℃, the main engine speed is 300r / min, the feed speed is 10r / min, and the vacuum degree of the vacuum section is 0.07MPa; the twin-screw extruder is extruded into filaments, then cooled with deionized water, and finally dried at room temperature for 24h to obtain the modified POE resin; (4) 100 parts of PVC resin, 2.5 parts of stabilizer liquid barium zinc, 13 parts of modified POE resin, 52.5 parts of trioctyl trimellitate, and 0.65 parts of heat-resistant crosslinking agent are accurately weighed according to the formula, put into a high-speed mixer and mix at a speed of 1350 rpm. When the temperature rises to 100°C, the material is discharged into a low-speed mixer at a speed of 85 rpm and cooled to 30°C before discharging; then the material is added to a double-roll open mill and mixed to form a sheet for 400 seconds at a roll temperature of 115°C; finally, the sheet is pressed in a molding machine at 170°C for 9 minutes and then cooled to obtain a transparent high-temperature resistant PVC crystal plate.
[0022] Example 3; (1) A three-necked flask was continuously filled with nitrogen. After the air was expelled, 60 parts of deionized water, 0.18 parts of anionic emulsifier OT, and 0.1 parts of potassium persulfate were added, and the mixture was heated and stirred at a stirring speed of 60 rpm and a heating rate of 10°C / min; when the temperature reached 70°C, 0.5 parts of a mixed solution of allyl methacrylate and 19 parts of 2-phenyl-1,3-butadiene were added dropwise for 1 hour. After the addition was completed, stirring was continued for 1 hour at a stirring rate of 250 rpm; a mixed solution of 5 parts of N-phenylmaleimide, 0.1 parts of potassium persulfate, and 4 parts of deionized water was added dropwise for 1 hour. After the addition was completed, stirring was continued for 1 hour to obtain an elastomer latex at a stirring rate of 250 rpm; (2) A three-necked flask is continuously filled with nitrogen, and 19 parts of elastomer latex, 50 parts of deionized water, and 0.1 parts of potassium persulfate are added. The mixture is heated and stirred to 70°C at a stirring speed of 60 rpm and a heating rate of 10°C / min. Then, 4 parts of glycidyl methacrylate are added dropwise for 30 minutes. After the reaction lasts for 1 hour, 4 parts of styrene are added dropwise for 30 minutes and maintained for 1 hour. After salting out and condensing with aluminum chloride solution, the filtrate is filtered and centrifuged at a speed of 20,000 rpm for 20 minutes. The filtrate is washed with deionized water three times and dried at 50°C for 8 hours to obtain a powdered polymer heat-resistant crosslinking agent. (3) Octamethyltetrasiloxane, hydroxy silicone oil and catalyst tetramethylammonium hydroxide silicon alkoxide were mixed in a weight ratio of 100:0.2:0.5, added to a three-necked flask, evacuated to 0.01 MPa at 60°C, then nitrogen was introduced, the temperature was raised to 100°C, and the reaction was continued for 3 hours; the temperature was raised to 120°C, and the reaction was continued for 3 hours; the temperature was raised to above 180°C and the evacuation was carried out for 1.5 hours to obtain terminal hydroxyl polydimethylsiloxane; 3 parts of maleic anhydride and 4 parts of terminal hydroxyl polydimethylsiloxane were weighed, added to a beaker, 20 parts of acetone were poured in to dissolve it, and the mixture was stirred at a speed of 120 rpm. Stir until completely dissolved; then pour the dissolved mixed solution into a high-speed mixer containing POE and stir for 5 minutes, the temperature is 300°C, the stirring speed is 400rpm, and the weight ratio of POE to the mixed solution is 100:1.5; finally, inject the mixed material into a twin-screw extruder, wherein the extruder barrel head temperature is 190°C, the main engine speed is 300r / min, the feed speed is 10r / min, and the vacuum degree of the vacuum section is 0.09MPa; the twin-screw extruder is extruded into filaments, then cooled with deionized water, and finally dried at room temperature for 24h to obtain the modified POE resin; (4) 100 parts of PVC resin, 3 parts of stabilizer liquid barium zinc, 18 parts of modified POE resin, 55 parts of trioctyl trimellitate, and 0.8 parts of heat-resistant crosslinking agent are accurately weighed according to the formula, put into a high-speed mixer and mix at a speed of 1450 rpm. When the temperature rises to 105°C, discharge the material into a low-speed mixer with a speed of 100 rpm and cool to 35°C before discharging; then add the material to a double-roll open mill and mix to form a sheet for 500 seconds at a roll temperature of 120°C; finally, the sheet is pressed in a molding machine at 180°C for 10 minutes and then cooled to obtain a transparent high-temperature resistant PVC crystal plate.
[0023] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (1) is different, and step (1) is changed to: nitrogen is continuously filled into a three-necked flask, and after the air is expelled, 60 parts of deionized water, 0.17 parts of anionic emulsifier OT, and 0.1 parts of potassium persulfate are added, and heated with stirring at a stirring speed of 60 rpm and a heating rate of 10°C / min; when the temperature is raised to 70°C, 0.4 parts of allyl methacrylate and 17.5 parts of a mixed solution of 2-phenyl-1,3-butadiene are added dropwise, and the addition time is 1 hour. After the addition is completed, stirring is continued for 1 hour at a stirring speed of 200 rpm to obtain an elastomer latex at a stirring speed of 200 rpm; the remaining steps are the same as those of Example 2.
[0024] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (1) is omitted and step (2) is changed to: nitrogen is continuously charged into a three-necked flask, 50 parts of deionized water and 0.1 parts of potassium persulfate are added, and then 3.75 parts of glycidyl methacrylate are added dropwise for 30 minutes; after reacting for 1 hour, 3.5 parts of styrene are added dropwise for 30 minutes and maintained for 1 hour; after salting out and condensing with aluminum chloride solution, the filtrate is filtered and centrifuged for dehydration at a centrifugal speed of 16000 rpm for 20 minutes, washed with deionized water three times, and dried at 50°C for 6.5 hours to obtain a powdered polymer heat-resistant crosslinking agent; the remaining steps are the same as those of Example 2.
[0025] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that there is no step (2), and step (4) is changed to: 100 parts of PVC resin, 2.5 parts of stabilizer liquid barium zinc, 13 parts of modified POE resin, 52.5 parts of trioctyl trimellitate, and 0.65 parts of elastomer latex are accurately weighed according to the formula, put into a high-speed mixer and mixed at a speed of 1350 rpm. When the temperature rises to 100°C, the material is discharged into a low-speed mixer with a speed of 85 rpm and cooled to 30°C before discharging; then the material is added to a double-roll open mill and mixed to produce a sheet for 400 seconds, and the roll temperature of the double-roll open mill is 115°C; finally, the sheet is pressed in a molding machine at 170°C for 9 minutes and then cooled to obtain a transparent high-temperature resistant PVC crystal plate; the remaining steps are the same as those in Example 2.
[0026] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that there is no step (3), and step (4) is changed to: 100 parts of PVC resin, 2.5 parts of stabilizer liquid barium zinc, 52.5 parts of trioctyl trimellitate, and 0.65 parts of heat-resistant crosslinking agent are accurately weighed according to the formula, put into a high-speed mixer and mixed at a speed of 1350 rpm. When the temperature rises to 100°C, the material is discharged into a low-speed mixer with a speed of 85 rpm and cooled to 30°C before discharging; then the material is added to a double-roll open mill and mixed to produce a sheet for 400 seconds, and the roll temperature of the double-roll open mill is 115°C; finally, the sheet is pressed in a molding machine at 170°C for 9 minutes and then cooled to obtain a transparent high-temperature resistant PVC crystal plate; the remaining steps are the same as those of Example 2.
[0027] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that step (3) is different, and step (4) is changed to: 100 parts of PVC resin, 2.5 parts of stabilizer liquid barium zinc, 13 parts of POE resin, 52.5 parts of trioctyl trimellitate, and 0.65 parts of heat-resistant crosslinking agent are accurately weighed according to the formula, put into a high-speed mixer and mix at a speed of 1350 rpm. When the temperature rises to 100°C, the material is discharged into a low-speed mixer with a speed of 85 rpm and cooled to 30°C before discharging; then the material is added to a double-roll open mill and mixed to produce a sheet for 400 seconds, and the roll temperature of the double-roll open mill is 115°C; finally, the sheet is pressed in a molding machine at 170°C for 9 minutes and then cooled to obtain a transparent high-temperature resistant PVC crystal plate; the remaining steps are the same as in Example 2.
[0028] Effect example Table 1 below shows the performance analysis results of a transparent high temperature resistant PVC crystal plate using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0029] Table 1
[0030] From the comparison of the experimental data of the high temperature resistance of the embodiment and the comparative example, it can be found that the present invention adds N-phenylmaleimide crosslinking agent during the emulsion polymerization of acrylic ester and 2-phenyl-1,3-butadiene monomer to ensure the optical properties of the crystal plate and improve its high temperature resistance. The crosslinking agent has a five-membered cyclic monomer with a 1,2-disubstituted vinyl structure. Embedding it in the polymer chain can increase the internal rotation resistance of the block, thereby improving the heat resistance of the polymer; in this process, a soap-free emulsion polymerization method is used to prepare a styrene-acrylic binary copolymer. Due to the block crosslinking characteristics, the common modified copolymer is avoided. The molecular chain of the added elastomer component contains a large number of unsaturated carbon-carbon double bonds, which leads to poor weather resistance and easy aging of the crystal plate during long-term use, thereby reducing its high temperature resistance; after obtaining the acrylic elastomer colloid, methacrylate glycidyl is grafted with styrene in steps to form a polymer, and this copolymer is added to the PVC resin as a heat-resistant crosslinking agent to improve its high temperature resistance. Secondly, octamethyltetrasiloxane is subjected to ring-opening polymerization in an alkaline environment to obtain terminal hydroxyl polydimethylsiloxane, and then the terminal hydroxyl polydimethylsiloxane is grafted and modified with maleic anhydride and POE resin matrix, and the heat resistance of the modified melt granulated POE resin is optimized, and then blended with PVC resin, the soft chain curling structure of octene and the crystalline ethylene chain are used as physical crosslinking points, and the two modified resins can form a dense network structure after blending to achieve a very excellent heat-resistant effect. From the comparison of the experimental data of the transparency of the embodiment and the comparative example, it can be found that the glycidyl methacrylate used in the present invention makes the epoxy group located on the side chain during ethylene polymerization to form an O-type polymer, which effectively ensures the light transmittance of the resin; in addition, the addition of the POE resin and various modifiers strictly selected by the present invention also ensures the transparency of the prepared crystal plate, and does not affect its light transmittance while improving the high temperature resistance.
[0031] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a transparent high temperature resistant PVC crystal plate, characterized in that: The method comprises the following preparation steps: (1) A three-necked flask is continuously filled with inert gas. After the air is expelled, 60 parts of deionized water, 0.16-0.18 parts of emulsifier, and 0.1 parts of potassium persulfate are added, and the mixture is heated and stirred at a speed of 60 rpm and a heating rate of 10°C / min. When the temperature reaches 70°C, a mixed solution of 0.3-0.5 parts of allyl methacrylate and 16-19 parts of 2-phenyl-1,3-butadiene is added dropwise. After the addition is completed, stirring is continued for 1 hour at a stirring rate of 150-250 rpm. A mixed solution of 3-5 parts of N-phenylmaleimide, 0.1 parts of potassium persulfate, and 3-4 parts of deionized water is added dropwise. After the addition is completed, stirring is continued for 1 hour at a stirring rate of 150-250 rpm to obtain an elastomer latex. (2) A three-necked flask is continuously filled with inert gas, and 17-19 parts of elastomer latex, 50 parts of deionized water, and 0.1 parts of potassium persulfate are added, and heated to 70°C with stirring at a speed of 60 rpm and a heating rate of 10°C / min; then 3.5-4 parts of glycidyl methacrylate are added dropwise for 30 minutes; after reacting for 1 hour, 3-4 parts of styrene are added dropwise for 30 minutes and maintained for 1 hour; after salting out and condensing with aluminum chloride solution, the filtrate is filtered and centrifuged for dehydration, washed with deionized water 3 times, and dried at 50°C for 5-8 hours to obtain a powdered polymer heat-resistant crosslinking agent; (3) Octamethyltetrasiloxane, hydroxy silicone oil and catalyst are mixed in a weight ratio of 100:0.1-0.2:0.3-0.5, added to a three-necked flask, evacuated to 0.01MPa at 60°C, then introduced nitrogen, heated to 80-100°C, reacted for 1-3h; heated to 100-120°C, continued to react for 1-3h; then heated to above 160-180°C and evacuated for 0.5-1.5h to obtain terminal hydroxyl polydimethylsiloxane; weigh 2-3 parts of maleic anhydride and 0.2-4 parts of terminal hydroxyl polydimethylsiloxane, add to a beaker Pour 20 parts of acetone into the mixture to dissolve it, and stir at 120rpm until it is completely dissolved; then pour the dissolved mixed solution into a high-speed mixer containing POE and stir for 5 minutes at a stirring speed of 400rpm; finally, inject the mixed material into a twin-screw extruder, wherein the extruder barrel head temperature is 170-190℃, the main engine speed is 300r / min, the feed speed is 10r / min, and the vacuum degree of the vacuum section is 0.05-0.09MPa; the twin-screw extruder is extruded into filaments, then cooled with deionized water, and finally dried at room temperature for 24h to obtain the modified POE resin; (4) 100 parts of PVC resin, 2-3 parts of stabilizer, 8-18 parts of modified POE resin, 50-55 parts of trioctyl trimellitate, and 0.5-0.8 parts of heat-resistant crosslinking agent are accurately weighed according to the formula, put into a high-speed mixer and mix at a speed of 1250-1450 rpm. When the temperature rises to 95-105°C, discharge the material into a low-speed mixer at a speed of 70-100 rpm and cool to 25-35°C before discharging; then add the material to a double-roll open mill and mix to produce a sheet. The roll temperature of the double-roll open mill is 110-120°C; finally, the sheet is pressed in a molding machine at 160-180°C for 8-10 minutes and then cooled to obtain a transparent high-temperature resistant PVC crystal plate.
2. The method for preparing a transparent high temperature resistant PVC crystal plate according to claim 1, characterized in that: The emulsifier in step (1) is an anionic emulsifier OT.
3. The method for preparing a transparent high temperature resistant PVC crystal plate according to claim 1, characterized in that: The dropping time in step (1) is 1 hour.
4. The method for preparing a transparent high temperature resistant PVC crystal plate according to claim 1, characterized in that: In the steps (1) and (2), the inert gas is nitrogen.
5. The method for preparing a transparent high temperature resistant PVC crystal plate according to claim 1, characterized in that: In step (2), the centrifugal speed is 12000-20000 rpm and the time is 20 min.
6. The method for preparing a transparent high temperature resistant PVC crystal plate according to claim 1, characterized in that: The catalyst in step (3) is tetramethylammonium hydroxide siliconate.
7. The method for preparing a transparent high temperature resistant PVC crystal plate according to claim 1, characterized in that: In the step (3), the weight ratio of POE to the mixed solution is 100:0.5-1.
5.
8. The method for preparing a transparent high temperature resistant PVC crystal plate according to claim 1, characterized in that: In step (3), the temperature of the high-speed stirrer during stirring is 200-300°C.
9. The method for preparing a transparent high temperature resistant PVC crystal plate according to claim 1, characterized in that: The stabilizer in step (4) is liquid barium zinc.
10. The method for preparing a transparent high temperature resistant PVC crystal plate according to claim 1, characterized in that: The mixing time in step (4) is 300-500s.
Citation Information
Patent Citations
Composition of PVC soft foamed crystal plates and preparation method for composition
CN108659370A
Polyvinyl chloride resin composition having transparency, high gloss, impact and weather resistance
US4035443A
